The communal justice. A comparative perspective of its constitutional treatment in the countries of the Andean Region - Arce Villar, César Alberto (2016)
Peruvian community justice is analyzed and also of the region, like countries which recognize constitutionality the legal pluralism, and provide similar standard treatment to the so-called special jurisdiction.